(untitled) (Research, Society and Development, 2024)
Considering the exponential increase in depressive and anxiety disorders in recent decades, it is possible to investigate the impact of adequate nutrition as a promising strategy in the prevention and treatment of anxiety and depression. Understanding the interconnection between food, mental health and emotional well-being, the present study aim to explore the relationship between eating patterns, specific nutrients and symptoms of anxiety and depression, elucidating the role of professional nutritionists in changing eating habits and prescription adequate diet. Thus, this is an experiment to understand the perceptions and eating practices of individuals diagnosed with anxiety and depression. Food preparations were selected that had, as their main ingredients, foods rich in nutrients and/or hormone precursor substances that act in mood regulation. Experimental articles and cross-sectional articles published between 2010 and 2024, in Portuguese and English, were also selected, relating the use of nutrients and specific food substances and the mitigation of depressive and anxiety symptoms on the ‘Scielo’ platforms; ‘EBSCOhost’; ’CAPES’ and ’UniCEUB Publications’ using the descriptors ’depression’, ’depression’ ’anxiety’, ’anxiety’, ’intestinal dysbiosis’, ’dysbiosis’, ’gut brain axis’, ’nutrients ’, ’nutrients’, associated with the Boolean operators AND and OR. From the result, it was observed the importance of adequate nutrition for good communication of the intestine-brain axis, as well as the contribution of the professional nutritionist to this type of treatment. relate the effect of micronutrients such as B vitamins, calcium and magnesium on the synthesis of psychoactive hormones and their effect on physical and mental well-being.